DL-3-n-Butylphthalide Attenuates Myocardial Hypertrophy by Targeting Gasdermin D and Inhibiting Gasdermin D Mediated Inflammation - Han, Bingjiang; Xu, Jiajun; Shi, Xiaowen; Zheng, Zhanxiong; Shi, Fengjie; Jiang, Fenfen; Han, Jibo (Frontiers in Pharmacology, 2021)
Pressure overload leads to a hypertrophic milieu that produces deleterious cardiac dysfunction. Inflammation is a key pathophysiological mechanism underpinning myocardial hypertrophy. DL-3-n-butylphthalide (NBP), a neuroprotective agent, also has potent cardioprotective effects. In this study, the potential of NBP to antagonize myocardial hypertrophy was evaluated in C57BL/6 mice in vivo and in rat primary cardiomyocytes in vitro. In mice, NBP treatment reduced cardiac hypertrophy and dysfunction in a transverse aortic constriction (TAC)-induced pressure overload model. In angiotensin (Ang) II-challenged cardiomyocytes, NBP prevents cell size increases and inhibits gasdermin D (GSDMD)-mediated inflammation. Furthermore, overexpression of GSDMD-N reduced the protective effects of NBP against Ang II-induced changes. Using molecular docking and MD simulation, we found that the GSDMD-N protein may be a target of NBP. Our study shows that NBP attenuates myocardial hypertrophy by targeting GSDMD and inhibiting GSDMD- mediated inflammation.